Students' Learning Independence Towards PAI Learning During The Covid-19 Pandemic in Class VIII of SMPN 2 Teluk Jambe East Karawang - Damayanti, Karlina; Kejora, Muhamad Taufik Bintang; Akil, Akil (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Independence is one aspect of a person's nature, so in studying the concept of independence it must be seen from the individual personality itself. Learning independence is the ability of students to realize their desires without depending on others. The purpose of this study was to determine the independence of students' learning towards PAI learning during the Covid-19 pandemic in class VIII of SMPN 2 Teluk Jambe Timur. This study uses a survey method. Survey research is research that takes a sample from one population and uses a questionnaire as a data collection tool. includes 3 aspects: (1) awareness in participating in learning, (2) responsibility in doing assignments, (3) motivation in learning PAI, (4) learning methodsvideo-based learning. Data analysis was performed using percentage analysis. The independence of students' learning towards PAI subjects is classified as good. because in these 4 aspects, many respondents answered agree more ... with the results of this study, it can be said that students have been able to adapt to the current application of online learning. However, teachers must always accompany students in the learning process so that students can better understand the material being studied and can increase learning independence, especially in PAI subjects.